Comparison of effects of clothing with different fiber compositions to body compositions during mountain climbing - De Leon, Christine Joyce M., author; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Dri-Fit fabric has become popularly used for outdoor sports, including mountain climbing. However, Dri-Fit fabric is quite expensive compared to other materials, including casual wear tops popularly used by many mountain climbing enthusiasts. This study aimed to determine whether or not regular casual wear can be considered as appropriate for mountain climbing, in comparison with clothing made from Dri-Fit fabric. A survey was first conducted to identify the two most popular casual wear used by selected mountain climbers from the University of the Philippines Diliman campus. The survey showed that these two casual wears were cotton blend knit top and polyester blend knit top. A mountain climbing experiment was then conducted where participants with the same anthropometry participated. Two participants wore the cotton blend knit top, two wore the polyester-blend knit top and two wore Dri-Fit knit top. The body temperatures and heart rates of the participants were recorded, compared, and analyzed. Findings showed that there were lesser differences on the body temperatures and heart rates of the participants wearing polyester blend knit top when compared with the participants wearing Dri-Fit knit top. On the other hand, there were greater differences on the body temperatures and heart rates of the participants wearing cotton blend knit tops when compared with the participants wearing Dri-Fit knit top. Participants also assessed that polyester blend knit top was more comfortable than the cotton-blend knit top. These findings suggest that polyester blend knit top is a better substitute to Dri-Fit than cotton blend. A continuing study with a bigger number of participants and other types of fiber blends used for outdoor sportswear is recommended.
Thesis (BS Clothing Technology) -- University of the Philippines Diliman, June 2016.
Keywords: Sports wear -- Effect on body composition